Negotiating Uneven Terrain with a Compliant Designed Unmanned Ground Vehicle Equipped with Locomotive Master‐Slave Operation. Issue 3 (19th February 2013) - Fukuoka, Yasuhiro; Hoshi, Katsuyuki; Kurosawa, Ryosuke
<x xml:space="preserve">Abstract</x> In recent years, a number operational unmanned ground vehicles (UGVs) have been developed that can negotiate irregular terrain. They have a number of degrees‐of‐freedom (DOF) giving them enhanced mobility, e.g., the ability to climb stairs and over obstacles. However, operating them remotely is complicated because their controllers are similar to conventional control pads or joysticks used in computer games or toys. It is hard for the operator to achieve an intuitive and natural feel, thus mistakes are common. To intuitively control the locomotion of a UGV with many DOFs, a master‐slave operation was implemented. A novel UGV called Kurogane, which consists of a typical crawler combined with a human‐like torso section, was developed. The torso section is controlled via a wearable controller interface. In addition, the UGV is equipped with models of muscle viscoelasticity and stretch reflex, called the involuntary autonomous adaptation system, inspired by the adaptive compliance of animals. The proposed system can autonomously and flexibly react and adapt to irregular terrain in real time. Therefore, the operation of Kurogane is simple and does not require great skill or precision. Experimental results show that it performs well over a fixed step, stairs, and rough outdoor terrain. © 2013 Wiley Periodicals, Inc.